ANALISIS REPONG DAMAR UNTUK MITIGASI BENCANA LONGSOR DI PESISIR BARAT LAMPUNG - Ahmad Taufiq; Pria Budi Tobing; Hesti Suhaja; Nandi Haerudin (Jurnal Samudra Geografi, 2023)
Landslides are one of the natural disasters that often result in loss of property and lives, as well as damage to facilities and infrastructure that can have an impact on the socio-economic conditions of the community, especially the people of the West Coast of Lampung. The landslide that occurred in Pesisir Barat Regency not only claimed lives but damaged residents' settlements and the Sumatra highway was cut off. Mitigation or preparedness to face landslides based on this community needs to be socialized, one of which is the existence of local wisdom that has been carried out by the community for generations one of them namely resin repong. Mitigation is carried out to minimize the impact of damage caused by landslides which have potential hazards, both structurally and non-structurally. The analytical method used is spatial analysis method, analysis using data interpreted in the form of maps. This analysis uses a software tool, namely ArcGIS.